Fungsi Komunikasi Kelompok dalam Progam Serap Gabah (Sergab) (Kasus pada Kelompok Tani Sri Rahayu Desa Purwosari, Kecamatan Babadan, Kabupaten Ponorogo, Jawa Timur) - SETYANING, ROSANA WIJAYANTI; SUARDI, I DEWA PUTU OKA; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.3, Juli 2018DO - 10.24843/JAA.2018.v07.i03.p12, 2018)
The Function of Group Communication in the Unhulled Rice Grains Subsidiary Program / Serap Gabah (Sergab), (Case in Sri Rahayu Farmers Group of Purwosari Village, Babadan Sub-District, Ponorogo Regency) The Serap Gabah Program (Sergab) is a national program set up to tackle the falling rice prices at the farmers' level at the time of harvest. The launching of the program is in line with the instruction of the President of Republic of Indonesia in cooperation with the rural military officer / Babinsa, Extension Agent/PPL, and the Logistics Agency of Bulog. As a new program in agriculture, Sri Rahayu Farmers Group in Purwosari Village, Babadan Sub-District, Ponorogo Regency is one of the farmer groups that received the Sergab program. This study aims to determine the application of group communication functions in Sergab program at Sri Rahayu Farmer Group of Purwosari Village, Sub-District of Babadan, Ponorogo Regency. The sampling technique is using simple random sampling method. Data analysis method used is descriptive analysis. Based on the descriptive analysis of group communication function in the Serap Gabah (Sergab) program at Sri Rahayu Farmer Group of Purwosari Village, Babadan Subdistrict, Ponorogo Regency is categorized as good enough with achievement score of 3.21. The farmer members of Sri Rahayu Farmer Group should be more active in taking the agricultural extension program of Sergab, so that they gain insights from the information given by the extension agents of PPL, chairman of Sri Rahayu Farmer Group is expected to actively encourage his members to follow Sergab program and Agricultural Extension as the activator of the Sergab program to further improve communication skills, especially persuasive communication, so that the persuasive communication function in the implementation of Sergab program can be well organized.